Rekonstruksjon av isutbreiing gjennom Weichsel i Grimsdalen, nordlige Rondane. - Klette, Jostein (The University of Bergen, 2006)
East-central southern Norway has for a long time been of interest for studying past ice-divides and ice sheet geometry of the ice sheets through the last glacial cycle. The existence of cold based non-erosive ice sheets here preserve landforms through several glaciations and make this area suitable for reconstructing earlier glacial stages. The aim of this master thesis is to reconstruct the glacial history of the Grimsdalen area through the last glacial cycle. The area shows few signs of glacial erosion because the ice sheets covering the area have been cold-based and non-erosive. The many glacio-fluvial accumulation- and erosion forms indicate a vertical downwasting of cold based and dynamically dead ice sheets. Periglacial features are common and well developed, which indicate that the area has been subaerialy exposed for longer time periods in a colder climate than at present. Dating of landforms using Optical Stimulated Luminscence (OSL) and exposure dating made it possible to give the different landforms absolute ages and to relate them to stadials through the Weichselian. During the deglaciation after the Saalian a large glaciofluvial fan was deposited in the central parts of Grimsdalen. This shows that there have been no warm based glaciers here during the Weichselian. The lack of dates from the Early- and Middle Weichselian make it difficult to reconstruct the glacial extent through these periods. Large marginal moraines in Gautådalen mark the Late Glacial Maximum (LGM) in the area showing a restricted vertical extent of the ice sheet during this period. The ice sheet was lying in the valleys north, west and east of the field area whereas parts of Grimsdalen were ice free during LGM. Meltwater channels show drainage from northwest and southwest into Grimsdalen indicating several domes. The fieldwork done in Grimsdalen suggests a thin and multidomed ice sheet with the existence of ice free areas throughout large parts of the Weichselian.